Design act, 2000 : along with the designs rules,2001 with short notes rules (New Delhi, 2002)
In1911 the Designs Act was passed by the then British Government in India, Since then extensive amendments have been made in the Designs Act. In the meanwhile India has made tremendous progress in the field of science and technology.
Keywords: Design-Laws and legislation